INTEGRATION OF "TRIZ AND QFD" FOR AN INNOVATIVE CAD DESIGN OF A LOW-COST REVERSIBLE GRAVITY PLOW PROTOTYPE - Rubio Valle, Alexis Enrique (2023)
Worldwide there are different designs of plows, however, these have their drive-in hydraulic systems raising the cost of production. The objective of this research was to design and optimize a prototype in CAD systems of a low-cost reversible gravity plow with three plowing discs that can be used by a low-power tractor (50 to 75 Hp). The design emphasizes the conceptual innovation and dimensioning of a novel system of mechanisms that, together, is capable of reversing the plow discs only with the action of gravity and the inertial masses that are produced when lifting the plow. For this innovative design, is incorporated the concepts of "Theory for Solving Inventive Problems" (Tieoriya Riesheniya Izobrietatielskij Zadach) (TRIZ) and "Quality Function Deployment" (QFD). For the dimensioning of the design, the moments of work in which the plow supports the greatest stress are considered: at the beginning of the plowing work and the lifting of the plow by the three-point hitch. Finally, extended reality technologies were used to create a virtual prototype that allows significant savings of time and money through the Solid Works program. The results indicate that the prototype is functional and reduces production and maintenance costs due to the simplicity of its components.